The authorities of law-enforcement organ: conceptual bases, theory qestions - Zlyvko, Stanislav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In this article theoretical aspects of the position of a in the authorities of law-enforcement organs are studied, the theoretical and methodological providing of administrative activity of a senior official in the authorities of Ukraine is characterized, the meaning and the concept of law-enforcement activity is disclosed, the requirements to the senior official as for the organizer of the administration.